Konstruksi Kerangka Konseptual Peranan Roh Kudus dalam PAK Menggunakan Taksonomi Bloom yang Diperbarui - Hanny Setiawan; Yonatan Alex Arifianto (IAKN Ambon, 2021)
A learning process is aimed toward outcomes. The desired outcomes are the initial point to construct the proper conceptual framework to describe the theoretical foundation of research. Spirituality and spiritual behaviour are two outcomes that Christian Education thinkers agreed upon from Old Testament to now. The meeting between Greeco-Roman and Jewish culture had somewhat changed the trajectory of how Christian Education developed. The Greek cognitive-based learning has influenced the initial Christian Education which is Jewish learning system. This article attempts to describe how spirituality, spiritual behaviour, and spiritual knowledge serve as the ultimate outcomes of Christian Education. The description will fit with the role of the Holy Spirit in the overall process of Christian Education in any given scope. As a result, this article will construct a conceptual framework that can be utilized further to design a biblical curriculum that is not merely cognitively measurable but also to provide an intentional outcome of spirituality and spiritual behaviour. The revised Bloom’s taxonomy will be used to bridge both worlds: the cognitive, and non-cognitive. In conclusion, this article shows that the supernatural work of Holy Spirit is not against the natural work of Holy Spirit through teacher and student relationships in Christian Education, but both work together. AbstrakProses pembelajaran ditujukan untuk mencapai suatu hasil. Hasil yang diinginkan merupakan titik awal untuk membangun kerangka konseptual yang tepat untuk mendeskripsikan landasan teoritis sebuah penelitian. Spiritualitas dan perilaku spiritual adalah dua hasil yang disepakati oleh para pemikir pendidikan Kristen dari zaman Perjanjian Lama hingga sekarang. Pertemuan antara budaya Yunani-Romawi dan Yahudi telah mengubah lintasan (trajectory) Pendidikan Kristen berkembang. Pembelajaran berbasis kognitif Yunani telah mempengaruhi sistem pembelajaran Yahudi. Artikel ini mencoba untuk menjelaskan bagaimana spiritualitas, perilaku spiritual, dan pengetahuan spiritual berfungsi sebagai hasil akhir dari Pendidikan Kristen. Hasil akhir tersebut dapat menggambarkan secara konseptual peran Roh Kudus dalam keseluruhan proses Pendidikan Kristen dalam lingkup apa pun. Sebagai hasil akhir, artikel ini akan menyajikan bangunan kerangka konseptual yang dapat digunakan lebih jauh untuk merancang kurikulum alkitabiah yang tidak hanya dapat diukur secara kognitif, tetapi juga untuk memberikan hasil yang disengaja dari spiritualitas dan perilaku spiritual. Taksonomi Bloom yang telah direvisi akan digunakan untuk menjembatani kedua dunia: kognitif dan non-kognitif. Artikel ini menunjukkan bahwa pekerjaan supernatural Roh Kudus tidak bertentangan dengan pekerjaan alami Roh Kudus melalui hubungan guru dan murid dalam pendidikan Kristen, tetapi keduanya bekerja sama.